Counteracting Poverty on Polish Lands after Both World Wars. A Comparative Analysis - Grata, Paweł (Studia Historiae Oeconomicae, 2025)
This article aimed to examine and compare ways of counteracting poverty in the Polish lands after both world wars. Based on available archival, printed sources and studies, the institutional foundations, methods, instruments, scope and effects of efforts to counteract the phenomenon of post-war poverty during the early post-war years were determined. It was necessary to assess the extent of this phenomenon and to perform a comparative analysis of efforts by the state, local governments and social organisations, focusing on similarities, differences and their sources. The chronological scope covers the years when welfare needs in Poland directly resulted from the effects of war (1918–1921 and 1944/45–1948). The research findings indicate that, both in the context of needs and the main methods employed, there were many similarities, as well as some differences. The similarities largely stem from comparable causes of post-war poverty and the similar scale of these phenomena, which primarily determined, the scope of required assistance. Notably, after 1944, the authorities could draw on the experience gained from activities carried out a quarter of a century earlier. Differences emerged due to specific needs, such as caring for returning inhabitants of the Kingdom of Poland "who were evacuated" in 1915, supporting Jews rescued from the Holocaust, or assisting inhabitants of bridgehead areas on the Vistula River living in extreme poverty after World War II. Additional differences involved the political climate surrounding rescue efforts. At the dawn of independence, the political background was limited to routine political disputes, whereas post-WWII efforts coincided with the forced power seizure by the communists, who, notably, imposed a form of ceasefire in social rescue activities. It is also worth noting that large-scale aid efforts after both world wars were generally inadequate, owing to the scale of needs, limited resources, organisational errors and decisions that did not always align with the real hierarchy of needs.